2017
DOI: 10.1080/17569370.2017.1313600
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating User-ship? Developing a Circular System for the Acquisition and Use of Baby Clothing

Abstract: This paper sets out to explore the significance of the production, sale and consumption of clothing as a product service system rather than as the more familiar 'shop-window' product offered for individual sale. While there are a number of studies of occupational clothing systems, relatively little is known about clothing systems tailored for the private market. This article presents a case study of a recently launched subscription service for baby clothing, which offered a range of eco-certified garments for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 21 publications
(21 reference statements)
0
32
0
Order By: Relevance
“…Adoption of the fashion subscription would also reduce the production and disposal of new fashion items, which in turn would reduce associated burdens on the environment. As qualitative studies have shown that consumers seem to take this into account when talking about fashion PSS, a third perceived value of the fashion subscription is its superior environmental performance (Armstrong, Niinimäki, Kujala, Karell, & Lang, ; Petersen & Riisberg, ). The assumption that PSS could tap into an emerging green consumer culture also featured early in the development of the field (Chian Tan, Cahalane, Tan, & Englert, ; Mont, ).H3 Perceived environmental benefit value is positively related to purchase intention.…”
Section: Perceived Value Hypothesesmentioning
confidence: 99%
See 4 more Smart Citations
“…Adoption of the fashion subscription would also reduce the production and disposal of new fashion items, which in turn would reduce associated burdens on the environment. As qualitative studies have shown that consumers seem to take this into account when talking about fashion PSS, a third perceived value of the fashion subscription is its superior environmental performance (Armstrong, Niinimäki, Kujala, Karell, & Lang, ; Petersen & Riisberg, ). The assumption that PSS could tap into an emerging green consumer culture also featured early in the development of the field (Chian Tan, Cahalane, Tan, & Englert, ; Mont, ).H3 Perceived environmental benefit value is positively related to purchase intention.…”
Section: Perceived Value Hypothesesmentioning
confidence: 99%
“…This has also been shown in fashion (Armstrong, Niinimäki, Kujala, Karell, & Lang, ; Armstrong, Niinimäki, Lang, & Kujala, ) and refers to the lack of choice of result‐oriented PSS. In the context of the fashion subscription, this would be reflected in receiving clothing that does not meet the preferred style or size of the consumer, reducing the attractiveness of the offer (Petersen & Riisberg, ).H5 Perceived style preference risk (PSPR) is negatively related to purchase intention.…”
Section: Perceived Risk Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations